The Effect of Soda Pulping Variables on Pulp Properties of Coir Fiber - Maria Ulfa; Koriatul Isnaini (Acta Chimica Asiana, 2020)
Abstract The potential use of coir fiber for pulping and papermaking has been investigated. This research aimed to study effects of pulping processing variables (temperature, pulping time, and alkali charge/solvent pulping) on the properties of pulp (residual lignin, alpha cellulose, kappa number and pulp yield) from coir fiber. For this purpose, the coir fibers were cooked using alkali charge (10 to 20% oven dried, as NaOH), pulping time from 60 to 120 min and temperature from 65 to 180oC. Results indicated that alkali charge and pulping time gave more impact on the properties of pulp than temperature. Pulping at high temperature, long pulping time, and high alkali charge resulted in decreasing of lignin, pulp yield, and kappa number but instead on alpha cellulose content. Keywords: coir, soda pulping, lignin